2019
DOI: 10.1093/esr/jcz066
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Trends in Adult Socio-Economic Resemblance between Former Schoolmates and Neighbouring Children

Abstract: Schools and residential neighbourhoods constitute key contexts of development beyond the family of origin. Yet, few prior studies address whether the overall impact of these childhood contexts on adult life chances has changed over time. In this article, we investigate changes in socio-economic resemblance between former schoolmates and neighbouring children using Norwegian administrative data covering three decades. We use cross-classified multilevel models to decompose the variance in children’s educational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
2
24
0
1
Order By: Relevance
“…For example, merely 0.5 percentage points of teacher absence separate students of the parents in the lower half of the earnings distribution from the parents in the top 1 percent. This equal exposure by socioeconomic background contrasts evidence from the US (Clotfelter et al, 2009), reflecting a modest degree of school and neighborhood segregation in Norway (Hermansen, Borgen, & Mastekaasa, 2020;Tammaru, Van Ham, Marcińczak, & Musterd, 2015). Despite negligible differences in exposure, teacher absence increases social inequality in long-term educational outcomes.…”
Section: Discussionmentioning
confidence: 69%
“…For example, merely 0.5 percentage points of teacher absence separate students of the parents in the lower half of the earnings distribution from the parents in the top 1 percent. This equal exposure by socioeconomic background contrasts evidence from the US (Clotfelter et al, 2009), reflecting a modest degree of school and neighborhood segregation in Norway (Hermansen, Borgen, & Mastekaasa, 2020;Tammaru, Van Ham, Marcińczak, & Musterd, 2015). Despite negligible differences in exposure, teacher absence increases social inequality in long-term educational outcomes.…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, the educational resources of coethnic neighbors seem to be more consequential for immigrant youth's future criminal behavior and educational careers than the local presence of immigrants from other origin countries and members of the native majority population. While the egalitarian character of Norwegian society likely provides lower-bound estimates on the role of adolescent neighborhood environments (Hermansen et al 2020), the general character of the underlying social mechanisms behind the patterns we observe-such as social control and normative pressure, transmission of aspirations, and help with homework or access to school-related information-suggests that these findings should be of relevance to other immigrant-receiving societies. observations, all cells report the mean value for each variable conditioned within the given country of origin.…”
Section: Discussionmentioning
confidence: 76%
“…Despite disadvantaged childhood origins, members of the second generation generally often experience upward mobility in terms of education and labor market outcomes when compared to their parents and their same-age native Norwegian peers (Bratsberg, Raaum and Røed 2012;Friberg 2019a;Hermansen 2016), but immigrant youth in several national-origin groups remain overrepresented in official crime statistics (Andersen, Holtsmark and Mohn 2017;Bratsberg et al 2012;Hermansen 2016;Skardhamar, Aaltonen and Lehti 2014). Moreover, prior research has found that the effects of immigrant concentration in schools on both majority and minority students' outcomes are modest once sorting is adequately addressed (Hermansen and Birkelund 2015) and spatial variation in children's life chances seems to be comparatively low in Norway (Hermansen, Borgen and Mastekaasa 2020). Overall, the mechanisms operating inside co-ethnic immigrant communities and local neighborhood settings are likely to be of a general character, although Norway's welfare-state context may provide a conservative case in terms of the magnitude of ethnic enclave effects.…”
Section: The Norwegian Contextmentioning
confidence: 99%
“…Children in immigrant households are highly concentrated in immigrant-dense and low-income areas when growing up, but childhood neighborhood segregation appears to be considerably less important than family background for ethnic disparities in education and adult earnings among second-generation immigrants (Hermansen 2016;Hermansen and Birkelund 2015). School and neighborhood contexts also seem to be of modest importance for socioeconomic attainment among natives (Hermansen, Borgen and Mastekaasa 2020).…”
Section: Immigration In the Norwegian Welfare Statementioning
confidence: 98%